Sex allocation according to multiple sexually dimorphic traits of both parents in the barn swallow (Hirundo rustica). (25th May 2015) - Romano, A.; Romano, M.; Caprioli, M.; Costanzo, A.; Parolini, M.; Rubolini, D.; Saino, N.
Abstract Parents should differentially invest in sons or daughters depending on the sex‐specific fitness returns from male and female offspring. In species with sexually selected heritable male characters, highly ornamented fathers should overproduce sons, which will be more sexually attractive than sons of less ornamented fathers. Because of genetic correlations between the sexes, females that express traits which are under selection in males should also overproduce sons. However, sex allocation strategies may consist in reaction norms leading to spatiotemporal variation in the association between offspring sex ratio (SR) and parental phenotype. We analysed offspring SR in barn swallows (Hirundo rustica) over 8 years in relation to two sexually dimorphic traits: tail length and melanin‐based ventral plumage coloration. The proportion of sons increased with maternal plumage darkness and paternal tail length, consistently with sexual dimorphism in these traits. The size of the effect of these parental traits on SR was large compared to other studies of offspring SR in birds. Barn swallows thus manipulate offspring SR to overproduce 'sexy sons' and potentially to mitigate the costs of intralocus sexually antagonistic selection. Interannual variation in the relationships between offspring SR and parental traits was observed which may suggest phenotypic plasticity in sex allocation and provides a proximate explanation for inconsistent results of studies of sex allocation in relation to sexual ornamentation in birds.